A pilot study: effect of irisin on trabecular bone in a streptozotocin-induced animal model of type 1 diabetic osteopathy utilizing a micro-CT - Mohsin,Sahar; Brock,Fiona; Kaimala,Suneesh; Greenwood,Charlene; Sulaiman,Mohsin; Rogers,Keith; Adeghate,Ernest (PeerJ, 2023)
Background Osteoporosis is a significant co-morbidity of type 1 diabetes mellitus (DM1) leading to increased fracture risk. Exercise-induced hormone ‘irisin’ in low dosage has been shown to have a beneficial effect on bone metabolism by increasing osteoblast differentiation and reducing osteoclast maturation, and inhibiting apoptosis and inflammation. We investigated the role of irisin in treating diabetic osteopathy by observing its effect on trabecular bone. Methods DM1 was induced by intraperitoneal injection of streptozotocin 60 mg/kg body weight. Irisin in low dosage (5 µg twice a week for 6 weeks I/P) was injected into half of the control and 4-week diabetic male Wistar rats. Animals were sacrificed six months after induction of diabetes. The trabecular bone in the femoral head and neck was analyzed using a micro-CT technique. Bone turnover markers were measured using ELISA, Western blot, and RT-PCR techniques. Results It was found that DM1 deteriorates the trabecular bone microstructure by increasing trabecular separation (Tb-Sp) and decreasing trabecular thickness (Tb-Th), bone volume fraction (BV/TV), and bone mineral density (BMD). Irisin treatment positively affects bone quality by increasing trabecular number p < 0.05 and improves the BMD, Tb-Sp, and BV/TV by 21–28%. The deterioration in bone microarchitecture is mainly attributed to decreased bone formation observed as low osteocalcin and high sclerostin levels in diabetic bone samples p < 0.001. The irisin treatment significantly suppressed the serum and bone sclerostin levels p < 0.001, increased the serum CTX1 levels p < 0.05, and also showed non-significant improvement in osteocalcin levels. Conclusions This is the first pilot study to our knowledge that shows that a low dose of irisin marginally improves the trabecular bone in DM1 and is an effective peptide in reducing sclerostin levels.
Keywords: Diabetes; Irisin; Streptozotocin; Trabecular bone; Micro-CT; Osteoporosis; Diabetic osteopathy; Sclerostin; Type 1 diabetes